Charles Dukes, the Deist and Labor Unionist who Shaped the Universal Declaration of Human Rights - O’Beara, Fearghas (The review of faith & international affairs, 2023)
Seventy five years after Charles Dukes represented the UK at the UN’s Human Rights Commission which drafted the Universal Declaration of Human Rights in 1947–1948, he is scarcely known compared with “major” figures of the drafting, like Roosevelt, Malik, and Cassin. With little formal education, the life-long trade union official had a very different profile from the jurists, academics, and diplomats who represented the other 17 states. Yet, Dukes’ intimate practical understanding of social and economic rights added an essential perspective, at a moment when the Cold War began to stir, including the battle for the heart of organized labor.